Contributions to a Regenerated Social Science: A Review - Fisk, Larry J. (Canadian Journal of Higher Education, 1976)
By 1965, behavioral social science had become a widely accepted approach to the scientific study of man and his politics. Any uncertainty as to what constituted a proper social science seemed to be raised most deeply by writers acquainted with the nature of physical science which most social science methodology seemed desparately to emulate. Recent comments by Nobel physicist Hideki Yukawa seem to indicate that little has changed in the physicist's scientific method in the last ten years and it would appear to be time to review those theories which prompted some radical reconsideration of the nature of both natural and social science over the last decade. The ideas which seem to lead to such a reconsideration include Werner Heisenberg's principle of uncertainty — that the observer's attempt to pin-point one phenomenon in nature disrupts or interferes with closely related phenomena; and Niels Bohr's principle of complimentarity where two seemingly different or contradictory theories when taken together offer a more complete understanding of a given phenomenon in the physical world. Michael Polanyi's notions of "tacit knowledge"and "indwelling" indicate that "we know more than we can tell" and that our view of isolated and detailed aspects of reality are rooted in a "prior knowledge"or even "involvement" in a larger whole. The capability of seeing or sharing in such larger wholes has been considered by humanistic psychologist Abraham Maslow as a measure of the scientist's maturity. A social scientist is open to more when he is a healthy person. Empathy, participation and man's purposefulness are the three human characteristics considered in this paper all of which seem to appear as the crux of a science of man by which all science must reinterpret its own methodology. To so interpret such characteristics rather than tailoring them to fit existing physical and behavioral scientific method and theory is to put certain ethical and political responsibilities of the social scientist at the very center of the nature, method and theory of our understanding of man and the science of man. The theories of Heisenberg, Bohr, Polanyi and Maslow support such a radical reinterpretation and the conclusion of the paper is that such a reinterpretation does not so much redefine social science in the light of natural science, but puts a reconsideration of the nature of man and science at center stage, so that a total regeneration of all science may be possible.